Assess the Influence of Artemisia Leaves Methanol - Aqueous Extract on Certain Biochemical Parameters in Albino Rats Alloxan-Induced Diabetic - Rikabi, Eman H. Al- (Jour Med Resh and Health Sci, 2023)
Background: For many generations, traditional medicine has utilised Artemisia L. as a treatment for a variety of ailments. Objectives: This study aims to examine the chemical composition of the methanol-aqueous extracts of Artemisia leaves and assess their impact on blood glucose, total antioxidants, and Vitamins A & E in normal and alloxan-induced diabetic rats. Artemisia leaves placed inside a soxhlet apparatus, as well as, the leaves were extracted using double distillation for four to five hours while water was used as the running solvent. Male and female albino rats weighing between 190 and 400 g were used in this research. The rats were split into three groups, each with ten rats. G1: groups with diabetes, G2: diabetic groups obtaining 150 mg/Kg body weight of methanol-aqueous extract daily, and G3: control groups. To induce diabetes, G1 Rats were fasted for the entire night and then intraperitoneally injected with freshly prepared 10% alloxan solution. Serum glucose (Glc) and total antioxidants were measured using Biolab assay kits, and vitamins A and E were measured using the enzyme-linked immunosorbent assay (ELISA). Results: After preparing the Artemisia extract of leaves in methanol and water, a chemical analysis was carried out. The extract of Artemisia leaves contained glycosides, flavonoids, submarines, alkaloids, tannins, saponins, and phenolic compounds, according to the results.. After fourteen days of oral treatment, diabetic rats treated with 150 mg/kg of Artemisia extract of leaves showed a significant reduction in blood glucose levels (P<0.05). On the other hand, on the final day of treatment, the administration of 150 mg/kg of Artemisia extract from leaves had no statistically significant increase in plasma total antioxidant levels (P<0.05) and concentration of Vitamins A and E (P<0.05) when compared with diabetic group. Conclusion: The study shows that oral administration of Artemisia extract significantly reduced hyperglycemia in diabetic rats in groups treated with 150 mg/Kg Artemisia extract of leaves as compared with diabetes groups. On the other hand, no differences in improvement in total antioxidant and Vitamin A& E levels. . ,